A comparative study of volatility breaks - Claudia Grote; Philip Bertram (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
In this paper we evaluate the performance of several structural break tests under various DGPs. Concretely we look at size and power properties of CUSUM based, LM and Wald volatility break tests. In a simulation study we derive the properties of the tests under shifts in the unconditional and conditional variance as well as for smooth shifts in the volatility process. Our results indicate that Wald tests have more power of detecting a change in the volatility than CUSUM and LM tests. This, however, goes along with the disadvantage of being slightly oversized. We further show that with huge outliers in the data the tests may exhibit non-monotonic power functions as the long-run variance of the squared return process is no longer finite. In an empirical example we determine the number and time of volatility breaks considering four equity and three exchange rate series. We find that in some situations the outcomes of the tests may vary substantially. Further we find fewer volatility breaks in the currency series than in the equity series.
Keywords: C22; C52; C53; 330; structural breaks; variance shifts; non-monotonic power